Upaya Indonesia Menjaga dan Meredam Konflik Diwilayah Laut NKRI Terutama Diwilayah Perbatasan Laut Cina Selatan Dikawasan Natuna Kepulauan Riau - Rahmadhan Tri Syahputra; Syafira Caesar Rani; Zada Idderigsa (Desentralisasi : Jurnal Hukum, Kebijakan Publik, dan Pemerintahan, 2025)
In writing this journal, I as the writer want to describe and present topics regarding issues that are often hot and often become conflicts in our country, the Republic of Indonesia, regarding the border area at the tip of the northern region of Indonesia or what is widely known to the general public is called "Indonesia's outermost islands" or what many of us know as Natuna Island, which is directly adjacent to neighboring countries and directly borders the South China Sea, this is also what often triggers conflicts over state regulations over maritime territories. As an example, we most often know about the number of fishermen from neighboring countries such as Vietnam, the Philippines and Myanmar who smuggle into the seas of the Republic of Indonesia illegally and without official permission and then take the wealth and marine products that Indonesia itself owns. This also causes things such as smuggling of goods and prohibited items to pass through urgent areas such as Natuna Island. The purpose of writing this journal is to describe the steps and efforts taken by the Indonesian state to defend and protect its territorial sovereignty and rights as they should. Based on several articles and news circulating in the Indonesian mass media regarding conflicts and problems that often occur and the most hot news is regarding Indonesia's sea which is considered strategic and has several times wanted to be claimed by neighboring countries.